2011
DOI: 10.1016/j.scitotenv.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and methylmercury concentrations in high altitude lakes and fish (Arctic charr) from the French Alps related to watershed characteristics

Abstract: Total mercury (THg) and methylmercury (MeHg) concentrations were measured in the muscle of Arctic charr (Salvelinus alpinus) and in the water column of 4 lakes that are located in the French Alps. Watershed characteristics were determined (6 coverage classes) for each lake in order to evaluate the influence of watershed composition on mercury and methylmercury concentrations in fish muscle and in the water column. THg and MeHg concentrations in surface water were relatively low and similar among lakes and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…They found large variations of the THg concentration in the fish (303 ± 187 ng g –1 of wwt) and suggested that elevation was better than age, trophic position, and growth rate to explain the difference. Marusczak et al measured Hg concentrations in 67 Arctic charr from 4 high-altitude lakes situated in the French Alps, where low methylation rate and poor food quality were suspected to be responsible for the low fish Hg levels (95–226 ng g –1 of wwt). Jenssen et al also attributed the low Hg concentrations (14–160 ng g –1 of wwt) in the mountain fish brown trout (Salmo trutta) and minnows (Phoxinus phoxinus) to their diets of low trophic level.…”
Section: Resultsmentioning
confidence: 99%
“…They found large variations of the THg concentration in the fish (303 ± 187 ng g –1 of wwt) and suggested that elevation was better than age, trophic position, and growth rate to explain the difference. Marusczak et al measured Hg concentrations in 67 Arctic charr from 4 high-altitude lakes situated in the French Alps, where low methylation rate and poor food quality were suspected to be responsible for the low fish Hg levels (95–226 ng g –1 of wwt). Jenssen et al also attributed the low Hg concentrations (14–160 ng g –1 of wwt) in the mountain fish brown trout (Salmo trutta) and minnows (Phoxinus phoxinus) to their diets of low trophic level.…”
Section: Resultsmentioning
confidence: 99%
“…Another French study of total mercury in eight shark species indicated that 5 out of 91 samples exceeded the ML of 1 000 µg/kg, ranging from 2 430 to 4 780 µg/kg (Velge et al, 2010). In 67 fish (Artic charr) from four lakes located in the French Alps, total mercury muscle concentrations did not exceed 500 µg/kg (Marusczak et al, 2011).…”
Section: Occurrence In Fish and Other Seafoodmentioning
confidence: 95%
“…Because of its importance for human health, Hg cycling has been studied in different aquatic systems (oceans, lakes, lagoons, rivers, and wetlands). Hg reactivity and transformation in lake and wetland ecosystems is well documented (Hintelmann 2010), but few studies have investigated Hg reactivity in extreme high-altitude ecosystems (Marusczak et al 2011;Qianggong et al 2014;Ribeiro Guevara et al 2008). Aquatic ecosystems located in the South American Altiplano region at 3800 m exhibit extreme thermal and solar irradiance diurnal variability including intense UV radiations (Blumthaler et al 1997;Zaratti et al 2003), contrasted seasonal hydrological cycles, as well as intense primary production (Aguirre et al 2014).…”
Section: Introductionmentioning
confidence: 99%